1998
DOI: 10.2337/diabetes.47.10.1562
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged oxidative stress impairs insulin-induced GLUT4 translocation in 3T3-L1 adipocytes.

Abstract: Prolonged exposure of 3T3-L1 adipocytes to micromolar concentrations of H2O2 results in an impaired response to the acute metabolic effects of insulin. In this study, we further characterized the mechanisms by which oxidative stress impairs insulin stimulation of glucose transport activity. Although insulin induced a 2.5-fold increase in plasma membrane GLUT4 content and a 50% reduction in its abundance in the low-density microsomal (LDM) fraction in control cells, oxidation completely prevented these response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
314
1
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 415 publications
(334 citation statements)
references
References 16 publications
12
314
1
7
Order By: Relevance
“…Oxidative stress occurring in obesity contributes to the oxidation of proteins in the plasma; these proteins may then undergo functional changes, in particular, loss of metabolic, enzymatic, and immunological properties (8). Protein thiol groups are the most susceptible to oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress occurring in obesity contributes to the oxidation of proteins in the plasma; these proteins may then undergo functional changes, in particular, loss of metabolic, enzymatic, and immunological properties (8). Protein thiol groups are the most susceptible to oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with an increase in oxidative stress, defined as an increased load of free radicals comprised of ROS and RNS generated during cellular metabolism (8). These free radicals are chemically reactive molecules that may damage cellular proteins, membranes, and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic (Moller et al 1996) and environmental (Paolisso et al 1999) factors may play a role. A recent line of evidence has indicated that increased generation of oxidative stress may also be a common pathogenetic factor mediating the appearance of IR (Bruce et al 2003;Ceriello et al 2004;Evans et al 2003;Rudich et al 1998;Talior et al 2003). In a variety of tissues, elevated glucose and free fatty acid levels result in the generation of ROS and, consequently, increased oxidative stress (Maddux et al 2001;Tretter and Adam-Vizi 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that oxidative stress may impair insulin action (Bruce et al 2003;Ceriello et al 2004;Evans et al 2003;Rudich et al 1998;Talior et al 2003). In particular, elevated free radical levels were found to impair insulin-induced glucose transporter-4 translocation in adipocytes, resulting in a degree of IR (Rudich et al 1998). However, the identity of the genes involved has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation